Production And Characterization Of An Antibiotically Active Compound(S) From A Local Marine Isolate, Bacillus Pulvifaciens Sbm-71 - Sabah Zrieq, Rafat Moh'd (2002)
One hundred and eighty bacterial isolates were obtained from marine samples collected from four different sites around Penang Island. A total of 18.3 % of the isolates secreted extracellular compounds which exhibited antimicrobial activity against at least one of the test microorganisms. The isolate SBm-71 which exhibited the highest antimicrobial activity was selected as a potential producer with a maximum antimicrobial activity of 21.5 U/ml. Isolate SBm-71 which was identified as Bacillus pulvifaciens secreted only extracellular antimicrobial compound(s).